2015
DOI: 10.1007/s11269-015-1035-6
|View full text |Cite
|
Sign up to set email alerts
|

A Heuristic Evolutionary Game Theoretic Methodology for Conjunctive Use of Surface and Groundwater Resources

Abstract: In this paper, a methodology based on a new heuristic evolutionary game is developed to determine evolutionary stable equilibrium (ESE) strategies for conjunctive surface and groundwater allocation to water users with conflicting objectives. The methodology provides reasonable and realistic framework to illuminate noncooperative behaviors of water users in the joint usage of surface and groundwater resources. The developed heuristic evolutionary game theoretic approach can be used for finding equilibrium in as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…However, they may instead neglect misaligned user incentives. Nonetheless, an increasing body of recent research combines both approaches to generate important new insights (Madani & Dinar, ; Müller, Müller‐Itten, et al, ; Parsapour‐Moghaddam et al, ). The example of groundwater overuse, taken from the field of water resources management, suggests that sociohydrologists have much to gain from stronger cross‐disciplinary interaction with economists when studying coupled human‐water systems.…”
Section: Problem 2: Theoretical Explanatory Powermentioning
confidence: 99%
See 1 more Smart Citation
“…However, they may instead neglect misaligned user incentives. Nonetheless, an increasing body of recent research combines both approaches to generate important new insights (Madani & Dinar, ; Müller, Müller‐Itten, et al, ; Parsapour‐Moghaddam et al, ). The example of groundwater overuse, taken from the field of water resources management, suggests that sociohydrologists have much to gain from stronger cross‐disciplinary interaction with economists when studying coupled human‐water systems.…”
Section: Problem 2: Theoretical Explanatory Powermentioning
confidence: 99%
“…First, most previous economic studies heavily idealize groundwater flows, whereas realistic representations of groundwater flows are often critical to understand user incentives. To our knowledge, two existing studies couple high‐fidelity (finite difference) numeric aquifer models and game theory (Müller, Müller‐Itten, et al, ; Parsapour‐Moghaddam et al, ). Both studies showed that user incentives are governed by complex groundwater flow patterns that would be missed by simpler models.…”
Section: Problem 2: Theoretical Explanatory Powermentioning
confidence: 99%
“…Compared with classical game theory, evolutionary game theory combines game theory with dynamic evolution process analysis, and it focuses more on the dynamics of strategy change (Weibull 1997). Evolutionary game theory aims at finding stable strategies in any area with conflict of interests (Parsapour-Moghaddam et al 2015). Tripartite stakeholders involved in quality supervision are bounded and rational, and they change and adjust their strategies dynamically by observing and comparing payoffs with others.…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary algorithms have been integrated with simulation model to tackle intricate SW and GW management model due to the effectiveness of solving non-linear and multimodal optimization problems (McPhee and Yeh, 2004;Yang, et al, 2009;Safavi and Esmikhani, 2013;Singh and Panda, 2013;Rothman and Mays, 2013;Wu et al, 2014;Parsapour-Moghaddam et al, 2015;Wu et al, 2016). Yang et al (2009) considered conflicting bi-objectives with the conjunctive use of GW and SW to achieve optimal pumping and recharge schemes.…”
Section: Introductionmentioning
confidence: 99%